Measurement and Comparison of Control Rod Worth of BTRR using Inhour Equation and Period reactivity conversion table (Journal of Bangladesh Academy of Sciences, 2017)
In a nuclear reactor, control rod is a very essential part and plays the elementary role in the reactor control during reactor start up, normal power operation, experimental research and shutdown. To perform all these operations safely, knowledge of differential and integral worth of the control rod is mandatory. In this study, the differential and integral worth curve of all control rods of BAEC TRIGA Research Reactor (BTRR) have been determined by using the positive period method. Reactor period was measured from 1.5 folding time, doubling time, 5 folding time respectively; and in the above three cases reactivity has also been calculated from INHOUR equation and period reactivity conversion table. The total worth of all control rods of BTRR are measured as 14.888 $, 14.672 $, 14.348 $ from INHOUR equation and 13.978 $, 13.672 $, 13.357 $ from period reactivity conversion table for 1.5 folding time, doubling time and 5 folding time respectively. The measured reactivity has also been compared with the previously measured reactivity and due to fuel burn up of the reactor expected lower values were observed.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 95-103, 2017